Testpraktikák enumerációja és az önértés dilemmái: (Tompa Andrea: Fejtől s lábtól) - Fodor, Péter (Studia Litteraria, 2023)
The story of Andrea Tompa’s novel takes place in Transylvania in the first decades of the 20th century. In the first half of the novel both protagonists are medical students, in the second half they are practicing doctors. rough using them as first-person narrators, the writer had the opportunity to use many of the discourses of medicine. This article analyses how they are implemented into the language of the novel and the way they can sometimes function on a metaphorical level. Furthermore, I examine how these discourses represent the change in the way modern humans relate to their own bodies and the bodies of the others.